Pengaruh Pemasaran Media Sosial dan Kualitas Produk terhadap Keputusan Pembelian: Studi pada Konsumen Jims Honey Cabang Kaliwungu - Syabilla Dwi Ramadhani; Nadia Dwi Irmadiani (Jurnal Media Administrasi, 2026)
The development of digital technology has encouraged businesses to utilize social media as an effective marketing tool, particularly in the fashion industry targeting Generation Z. In addition to digital promotional strategies, product quality is also an important factor influencing consumers’ purchase decisions. This study aims to analyze the effect of social media marketing and product quality on purchase decisions among consumers of Jims Honey Kaliwungu Branch. This research employed an explanatory type with a quantitative approach. The sample consisted of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using validity testing, reliability testing, multiple linear regression, t-test, F-test, and the coefficient of determination with the assistance of SPSS. The results show that social media marketing has a positive and significant effect on purchase decisions, with a t-value of 2.293 greater than the t-table value of 1.984 and a significance value below 0.05. Product quality also has a positive and significant effect on purchase decisions, with a t-value of 6.631 greater than the t-table value of 1.984 and a significance value below 0.05. Simultaneously, social media marketing and product quality have a significant effect on purchase decisions, with an F-value of 25.994 greater than the F-table value of 3.09 and a significance value below 0.05. The coefficient of determination of 0.349 indicates that both independent variables contribute 34.9% to purchase decisions. These findings confirm that product quality has a more dominant influence than social media marketing in encouraging purchase decisions among consumers of Jims Honey Kaliwungu Branch.